The intersections of global capital and family rhythms in truck driving: elucidating the Canadian trucking industry labour crisis. Issue 2 (4th May 2021) - Hanson, Natasha
ABSTRACT: The trucking industry in Canada, as well as other Western countries, is currently experiencing a significant labour shortage. This crisis has been explored through the lens of mobilities and in relation to how global logistics has impacted the supply chain. Building from these works, this article examines the Canadian provincial trucking industry through a rhythmanalysis framework, based on participant observation and interviews with truck drivers, employer representatives, and key informants. This analysis connects the large-scale rhythms of contemporary global capitalism to familial rhythms at the local level, examining how these rhythm patterns interrelate and the high potential for disruptions. The feminist intersectional focus of the analysis highlights gendered rhythms within the trucking industry and familial life, as well as power dynamics, particularly in relation to logistical power. The intersections of these, often incompatible, rhythms are sources of current pressures within the transportation industry and particularly the lives of truck drivers. These tensions within the lives of truck drivers are linked to recruitment issues and labour shortfalls the industry faces, not only within Canada but globally.